2011
DOI: 10.1093/ndt/gfr670
|View full text |Cite
|
Sign up to set email alerts
|

Periostin: novel tissue and urinary biomarker of progressive renal injury induces a coordinated mesenchymal phenotype in tubular cells

Abstract: These data demonstrate that periostin is a mediator and marker of tubular dedifferentiation and a promising tissue and urine biomarker for kidney injury in experimental models and in clinical renal disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
84
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(87 citation statements)
references
References 32 publications
(36 reference statements)
3
84
0
Order By: Relevance
“…Periostin is known to be expressed during renal development, but it is not expressed in the normal adult kidney [34]. Periostin is currently emerging as a marker of and therapeutic target for renal fibrosis, and related studies in various renal diseases have been published recently [13-19]. …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Periostin is known to be expressed during renal development, but it is not expressed in the normal adult kidney [34]. Periostin is currently emerging as a marker of and therapeutic target for renal fibrosis, and related studies in various renal diseases have been published recently [13-19]. …”
Section: Discussionmentioning
confidence: 99%
“…Extensive investigations of this protein have been conducted in various neoplasms, asthma, and cardiac diseases [9-12]. Recently, periostin has emerged as a player in the field of nephrology [13-20]. Periostin is known to be expressed mainly in the tubulointerstitial areas in renal fibrosis, and a relationship between urinary periostin level, tubular damage, autosomal dominant polycystic kidney disease, and chronic allograft nephropathy has been reported [13, 15, 16].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…13 Other investigators observed increased concentrations of urinary periostin in a small cohort of CKD patients. 14 We reported that periostin is highly upregulated during disease progression and inversely downregulated during regression in a model of hypertensive renal disease. 15 Although the above results indicate that periostin can be a new biomarker of renal disease progression, whether periostin participates in the development of CKD has not been examined.…”
mentioning
confidence: 90%
“…In addition, delivery of antisense oligonucleotides against periostin protected rats from the progression of renal disease in the L-NAME model [12]. Other investigators showed that periostinis overexpressed in additional experimental models of renal pathology and most importantly, it can be detected in the urine of human patients of CKD, even when albuminuria is within normal values [13].…”
Section: Periostinmentioning
confidence: 99%